Evaluation of Alternative Dietary Ingredients as a Sustainable and Ecological Solution for Meagre (Argyrosomus regius) Production in Earthen Ponds - Matias, Ana Catarina (2024)
Funding Information: This research was funded by INOVAQUA project (MAR-021.1.3-FEAMPA-00004). Publisher Copyright: © 2024 by the authors.